Effectiveness of Community-Based Educational Package on Stress Levels Among Postmenopausal Women - Rajinder Kaur,; Reetu Malhotra,; Chopra, Shivani (Scripta Medica, 2024)
Background/Aim: Postmenopausal women often face increased stress due to various physiological and psychological changes. This study aimed to analyse how effectively a community-based educational package (CBEP) reduces stress among postmenopausal women.Methods: A total of 200 postmenopausal women were assigned to either a control group (n = 100) or an experimental group (n = 100). The control group received routine care, while the experimental group engaged in a CBEP aimed at stress management. Stress levels were assessed before and after the intervention using a validated assessment tool and independent t-tests were used to compare the stress levels between the two groups and to evaluate changes in stress. Results: The pre-test stress levels showed no significant difference between the control and experimental groups (t = 1.184, p = 0.238), indicating similar stress levels at the start. However, post-test results demonstrated a significant reduction in stress for the experimental group (mean: 13.810 ± 2.339) compared to the control group (mean = 20.160 ± 3.281) (t = 15.762, p = 0.0001). Additionally, the gain in stress levels was significantly lower in the experimental group (0.150 ± 1.149) compared to the control group (6.000 ± 3.247) (t = 16.982, p = 0.0001). Conclusion: The results indicate that the community-based educational package effectively reduced stress levels among postmenopausal women, proving its efficacy as a non-pharmacological intervention. These findings advocate for the adoption of educational programs for managing stress in postmenopausal women and emphasise the need for further research to enhance these interventions for long-term efficacy.
Keywords: Postmenopause; Stress; Psychosocial intervention; Statistics; Data analysis